A bamboo crystal fiber filled biodegradable sheet and preparation method thereof

By combining bamboo crystal fiber with polyvinyl alcohol and crosslinking glycerin, combining chitosan and antioxidants, the problem of excessive use of chemical additives during processing of bamboo crystal fiber materials is solved, and the mechanical properties of the materials are improved. Biodegradability achieves efficient environmental protection and food safety.

CN118685010BActive Publication Date: 2024-12-27金达科技股份有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411158267.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-27
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

The existing bamboo crystal fiber materials require a large amount of chemical additives during processing, resulting in poor environmental protection effects and difficulty in increasing the filling amount and improving mechanical properties, affecting food safety and the environment.

Method used

Bamboo crystal fibers are combined with polyvinyl alcohol, combined with glycerin to form a three-dimensional network structure, and chitosan and antioxidants are introduced to improve compatibility and crystallinity through nucleating agents and coupling agents, and talc powder is added to improve High temperature resistance, forming bamboo fiber-filled biodegradable sheets.

Benefits of technology

The mechanical properties, aging resistance and biodegradability of the material are improved, with a degradation rate of more than 60.5%, and the pollution of the environment by chemical deep processing is avoided, ensuring food safety and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118685010B_ABST
    Figure CN118685010B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of biodegradable sheets, and specifically discloses a bamboo crystal fiber filled biodegradable sheet, wherein the raw materials include by mass: 40-60 parts of polylactic acid, 10-20 parts of polybutylene adipate / terephthalate, 40-60 parts of bamboo, 1-5 parts of polyvinyl alcohol, 10-20 parts of glycerol, 1-5 parts of polyaspartic acid, 0.01-0.1 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.01-0.02 parts of 1-hydroxybenzotriazole, 1-2 parts of chitosan, 1-3 parts of antioxidant, 1-3 parts of nucleating agent, 1-3 parts of coupling agent, 1-3 parts of dispersant, and 2-4 parts of talcum powder. The present invention also discloses a preparation method of the above-mentioned bamboo crystal fiber filled biodegradable sheet. The sheet obtained by the present invention has good mechanical properties, excellent aging resistance, and is easily degraded after being abandoned. After 72 days of degradation, its degradation rate can reach more than 60.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biodegradable sheets, and in particular to a bamboo crystal fiber filled biodegradable sheet and a preparation method thereof. Background Art

[0002] While polymer petroleum-based materials (such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, etc.) bring great convenience to people's lives, they also bring serious problems to society. They are not easy to degrade after being discarded. The increasing amount of plastic waste has caused great harm to the natural environment on which human beings depend for survival. It not only pollutes the soil and water sources, but also affects the absorption of nutrients and water by crops, which will lead to a reduction in crop yields.

[0003] Biodegradation refers to the degradation of materials caused by biological activities. The materials are gradually digested by microorganisms or certain organisms as a source of nutrition, resulting in quality loss, degradation of performance (such as physical properties), etc., and ultimately causing the materials to be decomposed into simpler compounds or elements.

[0004] Biodegradable materials can be disposed of with garbage or made into compost and returned to nature. As biodegradable materials reduce in size after degradation, the life of landfills can be extended. Biodegradable materials do not need to be incinerated, which can reduce the emission of harmful gases and reduce the harm to the environment, animals and plants.

[0005] Bamboo has the advantage of a short growth cycle, and can be used as a raw material to develop new biodegradable materials. Bamboo crystal fiber is a natural bio-based material with the advantages of light weight, high strength, large specific surface area and biodegradability. In addition, bamboo crystal fiber is a non-grain and non-wood material, which has greater promotion significance.

[0006] When bamboo-based biomaterials are used to prepare biodegradable materials, bamboo is chemically dissolved into viscose bamboo pulp, and then wet-spun to make fibers. Bamboo pulp fibers undergo chemical deep processing, and other chemical substances will be produced during the entire finishing process, causing pollution to the environment. Since bamboo crystal fiber has the characteristics of easy moisture absorption, wet elongation, and large plastic deformation, there is currently no mature process in the industry to increase the filling amount of bamboo crystal fiber materials, and most can only add 5-10%. At the same time, bamboo crystal fiber is hard, difficult to process, has low temperature resistance, and is easy to paste. The existing process will add a large amount of chemical additives during the processing process, which cannot achieve a truly environmentally friendly effect, seriously affecting the safety of product use, especially food safety. If harmful substances migrate, it will seriously affect your health. Summary of the invention

[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a bamboo crystal fiber filled biodegradable sheet and a preparation method thereof.

[0008] A bamboo crystal fiber filled biodegradable sheet material, the raw materials of which include, by mass, 40-60 parts of polylactic acid, 10-20 parts of polybutylene adipate / terephthalate, 40-60 parts of bamboo, 1-5 parts of polyvinyl alcohol, 10-20 parts of glycerol, 1-5 parts of polyaspartic acid, 0.01-0.1 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.01-0.02 parts of 1-hydroxybenzotriazole, 1-2 parts of chitosan, 1-3 parts of antioxidant, 1-3 parts of nucleating agent, 1-3 parts of coupling agent, 1-3 parts of dispersant and 2-4 parts of talc.

[0009] Preferably, the molecular weight of chitosan is 100,000-150,000, and the degree of deacetylation is 85-90%.

[0010] Preferably, the antioxidant is at least one of antioxidant BHT, antioxidant 164, antioxidant TPP, antioxidant 1010, and antioxidant 1076.

[0011] Preferably, the nucleating agent is at least one of N,N',N''-tricyclohexyl-1,3,5-benzamide and ethylene bisstearamide.

[0012] Preferably, the coupling agent is at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0013] Preferably, the coupling agent is silane coupling agent KH960.

[0014] Preferably, the dispersant is at least one of epoxidized soybean oil, stearic acid, and polyethylene wax.

[0015] Preferably, the mesh size of talcum powder is ≥1250 mesh and the whiteness is ≥90%.

[0016] The method for preparing the above-mentioned bamboo crystal fiber filled biodegradable sheet comprises the following steps:

[0017] S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 10-20 hours, and water and N,N-dimethylformamide are removed by rotary evaporation, and then freeze-dried to obtain composite granules;

[0018] S2, cutting the bamboo after felling, crushing and sieving, stirring at 40-60° C. for 4-10 min, adding polyvinyl alcohol and stirring for 5-20 min, heating to 95-100° C., adding glycerol and continuing stirring for 10-20 min, cooling to room temperature, and vacuum drying to obtain pretreated bamboo crystal fiber;

[0019] S3. Add polylactic acid to the pretreated bamboo crystal fiber, stir at 90-100° C. for 2-8 min, add composite granules, antioxidant, nucleating agent, coupling agent, dispersant, talcum powder, poly(butylene adipate / terephthalate) in sequence under stirring, continue stirring for 4-10 min, cool to 40-50° C., extrude granulate at 140-180° C., and then extrude and press into sheets.

[0020] Preferably, in S3, a twin-screw extruder is used for extrusion and tableting, wherein the extrusion temperature of the main machine is 150-200°C, and the temperature of the auxiliary machine is 180-220°C. Beneficial Effects

[0021] 1. The present invention adopts bamboo crystal fiber and polyvinyl alcohol as the compound, and the two have high affinity with each other; bamboo crystal fiber is used as the rigid skeleton, and polyvinyl alcohol is fully dispersed into the fiber structure, and then cross-linked with glycerol to form a three-dimensional network structure and combined with the bamboo crystal fiber structure, which can not only enhance the compatibility between the pretreated bamboo crystal fiber and polylactic acid, and has good processing technology, but also can make the sheet have good mechanical properties, excellent aging resistance, and easy to degrade after being discarded.

[0022] 2. The present invention combines chitosan with polyaspartic acid, and self-assembles to form core-shell nanoparticles under the driving force of hydrophobic action. Not only is the stability high, but also the affinity with pretreated bamboo crystal fiber and polylactic acid is good, so that the sheet material not only has antibacterial effect, can inhibit the growth of various bacteria, but also can cooperate with polyadipate / butylene terephthalate to have good ductility, and at the same time has excellent biodegradability after being discarded. It was found through experiments that the sheet material obtained by the present invention can reach a degradation rate of more than 60.5% after 72 days of degradation, and has excellent degradation performance.

[0023] 3. When extracting bamboo crystal fiber, the present invention directly grinds the bamboo and sieves it, effectively avoiding environmental pollution caused by chemical deep processing. The bamboo crystal fiber obtained by the present invention has a high moisture content, so it is cross-linked with polyvinyl alcohol and glycerol to effectively solve the characteristics of bamboo crystal fiber that it is easy to absorb moisture, wet elongation and large plastic deformation, and effectively improve the compatibility of bamboo crystal fiber and polylactic acid, polyadipate / butylene terephthalate, so that the material can be normally extruded and the processing technology is good.

[0024] 4. The present invention can effectively shorten the isothermal crystallization cycle time of polylactic acid, improve the crystallinity of polylactic acid, and increase the Vicat softening temperature of the material by introducing a nucleating agent. At the same time, the addition of talcum powder can improve the high temperature resistance of the material; while polybutylene adipate / terephthalate can improve the overall flexibility, improve the brittleness of the material, and make the resulting sheet stronger and more durable. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1This is a comparison chart of the tensile strength and elongation at break of the bamboo crystal fiber filled biodegradable sheets obtained in Example 5 and Comparative Examples 1-2.

[0026] Figure 2 The graph is a graph showing the biodegradability changes over 72 days using the bamboo crystal fiber filled biodegradable sheet obtained in Example 5 as the test material and TLC grade cellulose as the reference material. DETAILED DESCRIPTION

[0027] The present invention will be further explained below in conjunction with specific embodiments.

[0028] The chitosan used below was purchased from Jinan Derun Food Ingredients Co., Ltd. The batches used were tested before entering the factory: the average molecular weight was 120,000, and the average degree of deacetylation was 87.7%.

[0029] The talc powder used below was purchased from Liaoning Xinda Talc Group Co., Ltd., and the batches used were tested upon entering the factory: all passed a 1250-mesh sieve, with a whiteness of 92.4%. Example 1

[0030] A bamboo crystal fiber filled biodegradable sheet material, the raw materials of which include: 40kg of polylactic acid, 10kg of polybutylene adipate / terephthalate, 40kg of bamboo, 1kg of polyvinyl alcohol, 10kg of glycerol, 1kg of polyaspartic acid, 0.01kg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.01kg of 1-hydroxybenzotriazole, 1kg of chitosan, 1kg of antioxidant BHT, 1kg of ethylene bisstearamide, 1kg of silane coupling agent KH960, 1kg of epoxy soybean oil and 2kg of talc.

[0031] The method for preparing the above-mentioned bamboo crystal fiber filled biodegradable sheet comprises the following steps:

[0032] S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to 20 kg of N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to 5 kg of water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 10 hours. Water and N,N-dimethylformamide are removed by rotary evaporation, and composite granules are obtained by freeze drying;

[0033] S2, cut the bamboo after felling, crush it and sieve it, put it into a high-pressure mixing pot, stir it at a temperature of 40°C for 4 minutes, and the stirring speed is 300r / min, add polyvinyl alcohol and stir it for 5 minutes, heat it to 95°C, add glycerol and continue stirring for 10 minutes, cool it to room temperature, and vacuum dry it to obtain pretreated bamboo crystal fiber;

[0034] S3, adding polylactic acid to the pretreated bamboo crystal fiber, stirring at a temperature of 90°C for 2min, a stirring speed of 500r / min, and sequentially adding composite pellets, antioxidant BHT, ethylene bisstearamide, silane coupling agent KH960, epoxy soybean oil, talcum powder, polybutylene adipate / terephthalate under stirring, continuing stirring for 4min, cooling to 40°C, feeding into a twin-screw extruder, and extruding and granulating at 140°C to obtain pellets;

[0035] The pellets are fed into a twin-screw extruder for extrusion and sheeting, wherein the main extruder temperature is 150°C, the auxiliary extruder temperature is 180°C, cooled, calendered, and rolled. Example 2

[0036] A bamboo crystal fiber filled biodegradable sheet, the raw materials of which include: 60kg of polylactic acid, 20kg of polybutylene adipate / terephthalate, 60kg of bamboo, 5kg of polyvinyl alcohol, 20kg of glycerol, 5kg of polyaspartic acid, 0.1kg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.02kg of 1-hydroxybenzotriazole, 2kg of chitosan, 3kg of antioxidant TPP, 3kg of ethylene bisstearamide, 3kg of silane coupling agent KH960, 3kg of stearic acid and 4kg of talc.

[0037] The method for preparing the above-mentioned bamboo crystal fiber filled biodegradable sheet comprises the following steps:

[0038] S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to 30 kg of N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to 10 kg of water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 20 hours. Water and N,N-dimethylformamide are removed by rotary evaporation, and composite granules are obtained by freeze drying;

[0039] S2, cut the bamboo after felling, crush it and sieve it, put it into a high-pressure mixing pot, stir it at a temperature of 60°C for 10 minutes, and the stirring speed is 500r / min. Polyvinyl alcohol is added and stirred for 20 minutes. The temperature is raised to 100°C, glycerol is added and stirred for 20 minutes, and the temperature is cooled to room temperature, and vacuum dried to obtain pretreated bamboo crystal fiber;

[0040] S3, adding polylactic acid to the pretreated bamboo crystal fiber, stirring at a temperature of 100°C for 8min, a stirring speed of 700r / min, and sequentially adding composite pellets, antioxidant TPP, ethylene bisstearamide, silane coupling agent KH960, stearic acid, talcum powder, polybutylene adipate / terephthalate under stirring, continuing stirring for 10min, cooling to 50°C, feeding into a twin-screw extruder, and extruding and granulating at 180°C to obtain pellets;

[0041] The pellets are fed into a twin-screw extruder for extrusion and tableting, wherein the main extruder temperature is 200°C, the auxiliary extruder temperature is 220°C, and the pellets are cooled, calendered, and rolled. Example 3

[0042] A bamboo crystal fiber filled biodegradable sheet, whose raw materials include: 45kg of polylactic acid, 18kg of polybutylene adipate / terephthalate, 45kg of bamboo, 4kg of polyvinyl alcohol, 12kg of glycerol, 4kg of polyaspartic acid, 0.03kg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.018kg of 1-hydroxybenzotriazole, 1.3kg of chitosan, 2.5kg of antioxidant 164, 1.5kg of N,N',N''-tricyclohexyl-1,3,5-benzamide, 2.5kg of silane coupling agent KH960, 1.5kg of epoxy soybean oil and 3.5kg of talc.

[0043] The method for preparing the above-mentioned bamboo crystal fiber filled biodegradable sheet comprises the following steps:

[0044] S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to 22 kg of N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to 9 kg of water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 13 hours. Water and N,N-dimethylformamide are removed by rotary evaporation, and composite granules are obtained by freeze drying;

[0045] S2, cut the bamboo after felling, crush it and sieve it, put it into a high-pressure mixing pot, stir it at a temperature of 55°C for 6 minutes, and the stirring speed is 450r / min. Polyvinyl alcohol is added and stirred for 8 minutes. The temperature is raised to 99°C, glycerol is added and stirred for 12 minutes, and the temperature is cooled to room temperature. The pretreated bamboo crystal fiber is obtained by vacuum drying;

[0046] S3, adding polylactic acid to the pretreated bamboo crystal fiber, stirring at a temperature of 98°C for 4 minutes, a stirring speed of 650r / min, and sequentially adding composite pellets, antioxidant 164, N,N',N''-tricyclohexyl-1,3,5-benzamide, silane coupling agent KH960, epoxy soybean oil, talcum powder, polybutylene adipate / terephthalate under stirring, continuing stirring for 6 minutes, cooling to 47°C, feeding into a twin-screw extruder, and extruding and granulating at 150°C to obtain pellets;

[0047] The pellets are fed into a twin-screw extruder for extrusion and sheeting, wherein the main extruder temperature is 180°C, the auxiliary extruder temperature is 190°C, and the pellets are cooled, calendered, and rolled. Example 4

[0048] A bamboo crystal fiber filled biodegradable sheet, whose raw materials include: 55kg of polylactic acid, 12kg of polybutylene adipate / terephthalate, 55kg of bamboo, 2kg of polyvinyl alcohol, 18kg of glycerol, 2kg of polyaspartic acid, 0.07kg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.012kg of 1-hydroxybenzotriazole, 1.7kg of chitosan, 1.5kg of antioxidant 1076, 2.5kg of N,N',N''-tricyclohexyl-1,3,5-benzamide, 1.5kg of silane coupling agent KH960, 2.5kg of polyethylene wax and 2.5kg of talc.

[0049] The method for preparing the above-mentioned bamboo crystal fiber filled biodegradable sheet comprises the following steps:

[0050] S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to 28 kg of N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to 7 kg of water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 17 hours. Water and N,N-dimethylformamide are removed by rotary evaporation, and composite granules are obtained by freeze drying;

[0051] S2, cut the bamboo after felling, crush and sieve, put it into a high mixing pot, stir it at a temperature of 45 ° C for 8 minutes, the stirring speed is 350r / min, add polyvinyl alcohol and stir for 16 minutes, heat it to 96 ° C, add glycerol and continue stirring for 18 minutes, cool it to room temperature, and vacuum dry it to obtain pretreated bamboo crystal fiber;

[0052] S3, adding polylactic acid to the pretreated bamboo crystal fiber, stirring at a temperature of 92°C for 6 min, stirring at a speed of 550r / min, adding composite pellets, antioxidant 1076, N,N',N''-tricyclohexyl-1,3,5-benzamide, silane coupling agent KH960, polyethylene wax, talcum powder, polybutylene adipate / terephthalate in sequence under stirring, continuing stirring for 8 min, cooling to 43°C, feeding into a twin-screw extruder, extruding and granulating at 170°C to obtain pellets;

[0053] The pellets are fed into a twin-screw extruder for extrusion and tableting, wherein the main extruder temperature is 160°C, the auxiliary extruder temperature is 210°C, cooled, calendered, and rolled. Example 5

[0054] A bamboo crystal fiber filled biodegradable sheet, whose raw materials include: 50kg of polylactic acid, 15kg of polybutylene adipate / terephthalate, 50kg of bamboo, 3kg of polyvinyl alcohol, 15kg of glycerol, 3kg of polyaspartic acid, 0.05kg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.015kg of 1-hydroxybenzotriazole, 1.5kg of chitosan, 2kg of antioxidant 1010, 2kg of N,N',N''-tricyclohexyl-1,3,5-benzamide, 2kg of silane coupling agent KH960, 2kg of polyethylene wax and 3kg of talc.

[0055] The method for preparing the above-mentioned bamboo crystal fiber filled biodegradable sheet comprises the following steps:

[0056] S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to 25 kg of N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to 8 kg of water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 15 hours. Water and N,N-dimethylformamide are removed by rotary evaporation, and then freeze-dried to obtain composite granules;

[0057] S2, cut the bamboo after felling, crush it and sieve it, put it into a high-pressure mixing pot, stir it at a temperature of 50°C for 7 minutes, and the stirring speed is 400r / min. Add polyvinyl alcohol and stir it for 12 minutes, raise the temperature to 98°C, add glycerol and continue stirring for 15 minutes, cool it to room temperature, and vacuum dry it to obtain pretreated bamboo crystal fiber;

[0058] S3, adding polylactic acid to the pretreated bamboo crystal fiber, stirring at a temperature of 95°C for 5 minutes, a stirring speed of 600r / min, and sequentially adding composite pellets, antioxidant 1010, N,N',N''-tricyclohexyl-1,3,5-benzamide, silane coupling agent KH960, polyethylene wax, talcum powder, polybutylene adipate / terephthalate under stirring, continuing stirring for 7 minutes, cooling to 45°C, feeding into a twin-screw extruder, and extruding and granulating at 160°C to obtain pellets;

[0059] The pellets are fed into a twin-screw extruder for extrusion into sheets, wherein the main extruder temperature is 170°C, the auxiliary extruder temperature is 200°C, cooled, calendered, and rolled. Comparative Example 1

[0060] A bamboo crystal fiber filled biodegradable sheet, whose raw materials include: 50kg of polylactic acid, 15kg of polybutylene adipate / terephthalate, 50kg of bamboo, 3kg of polyvinyl alcohol, 15kg of glycerol, 3kg of polyaspartic acid, 1.5kg of chitosan, 2kg of antioxidant 1010, 2kg of N,N',N''-tricyclohexyl-1,3,5-benzamide, 2kg of silane coupling agent KH960, 2kg of polyethylene wax and 3kg of talc.

[0061] The method for preparing the above-mentioned bamboo crystal fiber filled biodegradable sheet comprises the following steps:

[0062] S1, cut the bamboo after felling, crush it and sieve it, put it into a high mixing pot, stir it at a temperature of 50°C for 7 minutes, and the stirring speed is 400r / min, add polyvinyl alcohol, polyaspartic acid and chitosan, stir for 12 minutes, heat it to 98°C, add glycerol and continue stirring for 15 minutes, cool it to room temperature, and vacuum dry it to obtain pretreated bamboo crystal fiber;

[0063] S2, adding polylactic acid to the pretreated bamboo crystal fiber, stirring at a temperature of 95°C for 5 min, stirring at a speed of 600r / min, adding antioxidant 1010, N,N',N''-tricyclohexyl-1,3,5-benzamide, silane coupling agent KH960, polyethylene wax, talcum powder, polybutylene adipate / terephthalate in sequence under stirring, continuing stirring for 7 min, cooling to 45°C, feeding into a twin-screw extruder, extruding and granulating at 160°C to obtain pellets;

[0064] The pellets are fed into a twin-screw extruder for extrusion into sheets, wherein the main extruder temperature is 170°C, the auxiliary extruder temperature is 200°C, cooled, calendered, and rolled. Comparative Example 2

[0065] A bamboo crystal fiber filled biodegradable sheet, whose raw materials include: 50kg of polylactic acid, 15kg of polybutylene adipate / terephthalate, 50kg of bamboo, 3kg of polyaspartic acid, 0.05kg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.015kg of 1-hydroxybenzotriazole, 1.5kg of chitosan, 2kg of antioxidant 1010, 2kg of N,N',N''-tricyclohexyl-1,3,5-benzamide, 2kg of silane coupling agent KH960, 2kg of polyethylene wax and 3kg of talc.

[0066] The method for preparing the above-mentioned bamboo crystal fiber filled biodegradable sheet comprises the following steps:

[0067] S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to 25 kg of N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to 8 kg of water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 15 hours. Water and N,N-dimethylformamide are removed by rotary evaporation, and then freeze-dried to obtain composite granules;

[0068] S2, cutting the bamboo after felling, crushing and sieving, sending it into a high-pressure mixing pot, stirring it at a temperature of 50° C. for 7 minutes, stirring at a speed of 400 r / min, heating it to 98° C., stirring to remove moisture to obtain pretreated bamboo crystal fiber;

[0069] S3, adding polylactic acid to the pretreated bamboo crystal fiber, stirring at a temperature of 95°C for 5 minutes, a stirring speed of 600r / min, and sequentially adding composite pellets, antioxidant 1010, N,N',N''-tricyclohexyl-1,3,5-benzamide, silane coupling agent KH960, polyethylene wax, talcum powder, polybutylene adipate / terephthalate under stirring, continuing stirring for 7 minutes, cooling to 45°C, feeding into a twin-screw extruder, and extruding and granulating at 160°C to obtain pellets;

[0070] The pellets are fed into a twin-screw extruder for extrusion into sheets, wherein the main extruder temperature is 170°C, the auxiliary extruder temperature is 200°C, cooled, calendered, and rolled.

[0071] With reference to GB / T 1040.4-2006 "Determination of tensile properties of plastics Part 4: Test conditions for isotropic and orthotropic fiber reinforced composite materials", the tensile strength and elongation at break of the bamboo crystal fiber filled biodegradable sheets obtained in Example 5 and Comparative Examples 1-2 were measured.

[0072] like Figure 1 As shown, the tensile strength of the bamboo crystal fiber filled biodegradable sheet obtained in Example 5 is the best. After t test, the tensile strength of the bamboo crystal fiber filled biodegradable sheet obtained in Example 5 is significantly better than that of Comparative Examples 1-2 (P < 0.05).

[0073] The bamboo crystal fiber obtained in Example 5 and Comparative Examples 1-2 was used to fill the biodegradable sheet and blister formed into a disposable lunch box.

[0074] With reference to GB 4806.7-2016 "National Food Safety Standard for Plastic Materials and Products for Food Contact", the above-mentioned disposable lunch boxes were tested for total migration (10% ethanol × 70℃ × 2h, 4% acetic acid × 70℃ × 2h, 65% ethanol × 70℃ × 2h) and discoloration test. The total migration of the three groups of disposable lunch boxes was ≤10mg / dm 3 , and the decolorization test was negative, both of which met the national standards.

[0075] The heavy metal and fluorine contents of the above-mentioned groups of disposable lunch boxes were measured with reference to GB / T 18006.3-2020 "General Technical Requirements for Disposable Degradable Tableware". The heavy metal and fluorine contents of the three groups of disposable lunch boxes were not detected.

[0076] The above-mentioned disposable lunch boxes were subjected to temperature and microwave resistance tests, and the results are shown in Table 1:

[0077] Table 1 Results of temperature and microwave resistance tests on each group of disposable lunch boxes

[0078]

[0079] In view of the fact that the safety, temperature resistance and microwave resistance test results of the three groups of disposable lunch boxes are similar, and the tensile strength of the sheet obtained in Example 5 is the highest, the present application uses the sheet obtained in Example 5 as the test material and thin layer chromatography grade cellulose as the reference material to conduct a 72-day composting degradation experiment (the dry weight ratio of compost to test material / reference material is about 6:1, and aeration treatment is carried out with de-CO2 air so that the oxygen concentration discharged from each compost container is not less than 6%, and the test is carried out at 58±2°C and in the dark; the CO2 release is determined by titration).

[0080] like Figure 2 As shown, the biodegradability of the reference material was 70.60% on the 45th day and 82.20% on the 72nd day; while the biodegradability of the test material was 45.60% on the 45th day and 60.50% on the 72nd day; the relative decomposition rate of the test material on the 72th day was 73.60%, which confirmed that the sheet material obtained by the present invention has good biodegradability.

[0081] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A bamboo crystal fiber filled biodegradable sheet, characterized in that: The raw materials include, by mass, 40-60 parts of polylactic acid, 10-20 parts of polybutylene adipate / terephthalate, 40-60 parts of bamboo, 1-5 parts of polyvinyl alcohol, 10-20 parts of glycerol, 1-5 parts of polyaspartic acid, 0.01-0.1 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.01-0.02 parts of 1-hydroxybenzotriazole, 1-2 parts of chitosan, 1-3 parts of antioxidant, 1-3 parts of nucleating agent, 1-3 parts of coupling agent, 1-3 parts of dispersant, and 2-4 parts of talc. Prepared by the following steps: S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 10-20 hours, and water and N,N-dimethylformamide are removed by rotary evaporation, and then freeze-dried to obtain composite granules; S2, cutting the bamboo after felling, crushing and sieving, stirring at 40-60° C. for 4-10 min, adding polyvinyl alcohol and stirring for 5-20 min, heating to 95-100° C., adding glycerol and continuing stirring for 10-20 min, cooling to room temperature, and vacuum drying to obtain pretreated bamboo crystal fiber; S3. Add polylactic acid to the pretreated bamboo crystal fiber, stir at 90-100° C. for 2-8 min, add composite granules, antioxidant, nucleating agent, coupling agent, dispersant, talcum powder, poly(butylene adipate / terephthalate) in sequence under stirring, continue stirring for 4-10 min, cool to 40-50° C., extrude granulate at 140-180° C., and then extrude and press into sheets.

2. The bamboo crystal fiber filled biodegradable sheet according to claim 1, characterized in that: The molecular weight of chitosan is 100,000-150,000, and the degree of deacetylation is 85-90%.

3. The bamboo crystal fiber filled biodegradable sheet according to claim 1, characterized in that: The antioxidant is at least one of antioxidant BHT, antioxidant 164, antioxidant TPP, antioxidant 1010, and antioxidant 1076.

4. The bamboo crystal fiber filled biodegradable sheet according to claim 1, characterized in that: The nucleating agent is at least one of N,N',N''-tricyclohexyl-1,3,5-benzamide and ethylene bisstearamide.

5. The bamboo crystal fiber filled biodegradable sheet according to claim 1, characterized in that: The coupling agent is at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

6. The bamboo crystal fiber filled biodegradable sheet according to claim 1 or 5, characterized in that: The coupling agent is silane coupling agent KH960.

7. The bamboo crystal fiber filled biodegradable sheet according to claim 1, characterized in that: The dispersant is at least one of epoxidized soybean oil, stearic acid and polyethylene wax.

8. The bamboo crystal fiber filled biodegradable sheet according to claim 1, characterized in that: The mesh size of talcum powder is ≥1250 mesh and the whiteness is ≥90%.

9. A method for preparing a bamboo crystal fiber filled biodegradable sheet as claimed in any one of claims 1 to 8, characterized in that: The steps include: S1. Under nitrogen protection, polyaspartic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1-hydroxybenzotriazole are added to N,N-dimethylformamide and stirred evenly to obtain a prefabricated material; chitosan is added to water and stirred evenly, and then added dropwise to the prefabricated material in a stirred state, and stirring is continued for 10-20 hours, and water and N,N-dimethylformamide are removed by rotary evaporation, and then freeze-dried to obtain composite granules; S2, cutting the bamboo after felling, crushing and sieving, stirring at 40-60° C. for 4-10 min, adding polyvinyl alcohol and stirring for 5-20 min, heating to 95-100° C., adding glycerol and continuing stirring for 10-20 min, cooling to room temperature, and vacuum drying to obtain pretreated bamboo crystal fiber; S3. Add polylactic acid to the pretreated bamboo crystal fiber, stir at 90-100° C. for 2-8 min, add composite granules, antioxidant, nucleating agent, coupling agent, dispersant, talcum powder, poly(butylene adipate / terephthalate) in sequence under stirring, continue stirring for 4-10 min, cool to 40-50° C., extrude granulate at 140-180° C., and then extrude and press into sheets.

10. The method for preparing the bamboo crystal fiber filled biodegradable sheet according to claim 9, characterized in that: In S3, a twin-screw extruder is used for extrusion and tableting, wherein the extrusion temperature of the main machine is 150-200°C, and the temperature of the auxiliary machine is 180-220°C.

Citation Information

Cited By

  • Full-degradable high-filling bamboo fiber composite material and preparation method thereof

    CN122521138A

  • A fully degradable high-filling bamboo fiber composite material and a preparation method thereof

    CN122521138B